Literature as a Transformation of Social Education in Supporting SDGs in Indonesia - Saniro, Roma Kyo Kae; Hawa, Andina Meutia; Pratiwi, Dyani Prades; Sukmawati, Noni (IAIN Madura, 2025)
Literature plays a crucial role as a medium for social education transformation, particularly in supporting sustainable development in Indonesia. This study aims to explore how local literary works can be integrated into education through the lens of literary anthropology to strengthen character formation and promote the values aligned with sustainable development goals. The research focuses on two contemporary Indonesian novels rooted in local cultures, analyzing their potential to convey ethical, cultural, and social values relevant to inclusive and transformative education. Using a qualitative descriptive method, the study applies content analysis and thematic interpretation guided by literary anthropology. Two novels—Gampo: Robohnya Rumah Gadang Kami and Negarabatin: Negeri di Balik Bukit—were selected as the primary corpus. Cultural symbols, narrative structures, and value systems embedded in these texts were examined and interpreted in relation to educational objectives and sustainable development themes. The findings reveal that both novels reflect rich local wisdom, including values such as communal cooperation, religious devotion, familial responsibility, and indigenous leadership. These values are strongly aligned with core educational goals, especially those related to quality education, social inclusion, and peaceful institutions. Cultural symbols like the Minangkabau rumah gadang and the Lampung term uyung serve not only as literary elements but also as pedagogical tools for character education. Furthermore, the study demonstrates how these texts can be integrated into contextual learning models, encouraging critical literacy, ethical reasoning, and cultural empathy among students. The study concludes that local literature is not merely a cultural artifact but a strategic educational resource capable of advancing inclusive and value-based education. By adopting literary anthropology as both an interpretive and pedagogical framework, the research contributes to the design of culturally grounded curricula that support transformative learning and sustainable development in Indonesia.